Aktivitas Fisik Jalan Santai Untuk Penanganan Ketidakstabilan Kadar Glukosa Darah Pada Pasien Diabetes Mellitus - Faridatul Istibsaroh; Fadhilatul Mila; Ahmad Zaini Arif; Mei Lestari Ika Widyyati (Universitas Nazhatut Thullab Al- Muafa Sampang, 2023)
Introduction: Instability of blood glucose levels (hyperglycemia) is a condition of increased blood glucose levels that can take place acutely and chronically caused by heredity, obesity, overeating, lack of exercise, and lifestyle changes. One of the diseases that can cause unstable blood glucose levels is Diabetes Mellitus. In the case of Diabetes Mellitus, it is caused by an increase in blood glucose levels which is characterized by the absence of insulin in the body accompanied by the classic symptoms of Diabetes Mellitus, namely polyuria, polydipsia, polyphagia. The Aim of this study is to describe the physical activity of leisure walking to reduce blood glucose levels in patients with Diabetes Mellitus. This research method uses a descriptive case study method by analyzing in depth a research object whose unit of analysis is individual from assessment, diagnosis, intervention, implementation and evaluation. Two respondents with a medical diagnosis of Diabetes Mellitus were selected using a purposive sampling technique. Results: The results showed that on the third day of R1, patients said they were tired or lethargic (decreased), patients said they had increased thirst (decreased), high blood glucose levels (improved), GDA: 90 mg/dL the problem was resolved. Whereas in patient R2 the patient said he was tired or lethargic (decreased) and had high blood glucose levels (improved), GDA: 165 mg/dL and the problem was resolved. Conclusion: After being given nursing care with leisurely walking physical activity to 2 patients, it can be concluded that this therapy can reduce blood glucose levels in Diabetes Mellitus patients.